Thermosensitive block copolymer [(PNIPAM)-b-(Glycine)] thin film as protective layer for drug loaded mesoporous silica nanoparticles. (24th October 2017) - Amgoth, Chander; Joshi, Suman
Abstract: Synthesis and characterization of [(PNIPAM)-b-(Gly)] and mesoporous silica nanoparticles (MP-SiO2 NPs) were carried out separately and used to develop [(PNIPAM)-b-(Gly)]-(MP-SiO2 NPs). The synthesized MP-SiO2 NPs were meso porous in nature. The size of SiO2 NPs is in the range of 180–250 nm (in diameter) with an average pore size of 2.8 nm within the particles. Interestingly, these mesoporous SiO2 NPs were loaded with anticancer drug (ITM-imatinib mesylate) fallow by the incubation for 24 h at RT. However, ITM loaded MP-SiO2 NPs were capped or covered with synthesized [(PNIPAM)-b-(Gly)] thin film. Here, thin film acts as protective layer for drug loaded MP-SiO2 NPs, with that leakage of drug molecules throughout its transport pathway can be avoided. Significantly, thermosensitive [(PNIPAM)-b-(Gly)] polymer thin film depletes at body temperature ( 37 °C) and drug molecules come out from the pores of SiO2 NPs. However, developed [(PNIPAM)-b-(Gly)]-(MP-SiO2 NPs) is compatible and used for cell inhibition studies. After 24 h treatment, drug ITM released from [(PNIPAM)-b-(Gly)]-(MP-SiO2 NPs) shows significant (>90%) inhibition on leukemia blood cancer (K562) cells.